Effect of concurrent explosive strength and endurance training on sprint performance before and after a 5-min time trial - Müller, B.; Steiner, T.; Wehrlin, J. P. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
A fast starting phase can be crucial to overall performance in MTB Cross Country competition whereas in road cycling it is the final sprint which can determine whether someone is successful or not. This variable competition intensity with many needed accelerations creates high demands in muscular strength (Yamamoto et al., 2010). The purpose of this study was to examine the effect of explosive strength training on a 10 s sprint performance at rest and after a 5-min time trial (TT). Methods: Eighteen male adolescent cyclists (age 15.0 ± 0.5 yr) were matched to pairs and assigned either a combined strength and endurance group (S&E; n = 9; VO2peak 64.0 ± 5.1 ml/kg/min) or an endurance group (E; n = 9; VO2peak 64.7 ± 1.8 ml/kg/min). One-third of the training sessions in the S&E group consisted of explosive strength training. During the 6-week intervention the training load and duration as well as the intensity distribution were the same for both S&E and E groups. The following parameters were measured before and after the training intervention: Sprint performance for 10 s at rest and after a 5-min TT recording Peak power (Ppeak) and mean power for 10 s (P10s), power during the 5-min TT, VO2peak, and squat jump (SJ) performance. Results: Results after the intervention showed no significant differences within the groups for Ppeak (S&E +1.3 ± 5.8%; E -3.0 ± 5.9% ) or within the E group alone for P10s (-1.5 ± 5.2%). The S&E group showed +3.8 ± 4.4% higher P10s at rest. After the TT, the E group improved Ppeak (+15.7 ± 20.4%) and P10s (+16.1 ± 20.7%), whereas in the S&E group only P10s improved (+16.5 ± 16.1%) significantly. Both groups improved their TT performance (S&E +11.5 ± 5.4%; E +8.0 ± 7.0%). The S&E group improved VO2peak (+6.0 ± 3.6%) and SJ performance (+7.8 ± 5.2%). No changes were seen in the E group in these parameters (VO2peak +2.2 ± 3.2%; SJ +1.9 ± 5.8%). The development of VO2peak and SJ performance before and after the intervention was different between the two groups. Discussion: Concurrent explosive strength and endurance training showed an improvement in total sprint performance during 10 s at rest without compromising TT performance. In addition, the S&E group improved their explosive strength ability as well as VO2peak. Accordingly, in bike disciplines where a high intensity start phase is crucial to performance, combined strength and endurance training can be recommended as part of the yearly training plan. Furthermore, negative effects of strength training on endurance performance in this age group are not to be expected.